(untitled) - Ngô, Ngọc Hải (Cần Thơ, 2018)
The present research is conducted to obtain two research aims. The first aim is to find out the teachers’ perception of the implementation of the individualized learning model. The second aim is to investigate the benefits and difficulties teachers face when they implement the individualized learning model in their classrooms.
Keywords: Tiếng Anh,English language; Học và dạy học,Study and teaching